2021
DOI: 10.3390/v13091722
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of SARS-CoV-2 Nsp10-Nsp16 Methyltransferase

Abstract: The ongoing COVID-19 pandemic exemplifies the general need to better understand viral infections. The positive single-strand RNA genome of its causative agent, the SARS coronavirus 2 (SARS-CoV-2), encodes all viral enzymes. In this work, we focused on one particular methyltransferase (MTase), nsp16, which, in complex with nsp10, is capable of methylating the first nucleotide of a capped RNA strand at the 2′-O position. This process is part of a viral capping system and is crucial for viral evasion of the innat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 49 publications
0
24
0
2
Order By: Relevance
“…This structure consists of an N 7-methylguanosine linked by a 5′-5′-triphosphate bridge to the 5′-terminal nucleotide (adenosine in CoVs) (cap 0: 7m GpppA), which can be further methylated at its 2′- O position (cap 1: 7m GpppA m ). 5 , 6 Specifically, N 7-methylation of the viral RNA cap plays a key role in the translation of viral RNA into proteins. Furthermore, inhibition of the SARS-CoV-2 nsp14 N 7-methyltransferase (MTase) blocks the enzymatic cascade of viral RNA methylations, as the 2′- O -MTase (nsp16) only recognizes N 7-methylated cap substrates.…”
Section: Introductionmentioning
confidence: 99%
“…This structure consists of an N 7-methylguanosine linked by a 5′-5′-triphosphate bridge to the 5′-terminal nucleotide (adenosine in CoVs) (cap 0: 7m GpppA), which can be further methylated at its 2′- O position (cap 1: 7m GpppA m ). 5 , 6 Specifically, N 7-methylation of the viral RNA cap plays a key role in the translation of viral RNA into proteins. Furthermore, inhibition of the SARS-CoV-2 nsp14 N 7-methyltransferase (MTase) blocks the enzymatic cascade of viral RNA methylations, as the 2′- O -MTase (nsp16) only recognizes N 7-methylated cap substrates.…”
Section: Introductionmentioning
confidence: 99%
“…This class of enzymes uses a common bimolecular nucleophilic substitution (S N 2) methyl transfer mechanism, where S-adenosyl-L-methionine (AdoMet or SAM) usually donates a methyl to nitrogen, oxygen, or carbon atoms [ 30 ]. In the present case, nsp16 methylates the 5′ end of the mRNA, converting the mRNA from an uncapped (named as cap-0) to the capped (named as cap-1) form by transferring a methyl group to the first nucleotide, adenosine, on the ribose 2′- O position of the newly forming mRNA strand [ 19 ]. Interestingly, Benoni et al [ 19 ] showed that nsp16-nsp10 complex can also methyl-ate the first guanosine-5′-triphosphate (GTP) nucleobase of pre-capped mRNA, which is the natural substrate of nsp14.…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, nsp16 methylates the 5′ end of the mRNA, converting the mRNA from an uncapped (named as cap-0) to the capped (named as cap-1) form by transferring a methyl group to the first nucleotide, adenosine, on the ribose 2′- O position of the newly forming mRNA strand [ 19 ]. Interestingly, Benoni et al [ 19 ] showed that nsp16-nsp10 complex can also methyl-ate the first guanosine-5′-triphosphate (GTP) nucleobase of pre-capped mRNA, which is the natural substrate of nsp14. In this study, 100 ns of molecular dynamics (MD) simulations were carried out for nsp16-A and nsp16-G systems to gain insight into the atomistic view of pre-reactive nsp10-nsp16-SAM-m7GpppA-RNA and nsp10-nsp16-SAM-m7GpppG-RNA complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the important role of ORF9b in the suppression of host innate immunity by disruption of interferon responses [23,24], we are convinced that this antibody will contribute to its further characterization and understanding. Similarly, our antibody to nsp10, an intriguing protein known to form complex with nsp16 that is involved in methylation of a capped RNA strand and necessary for viral immune evasion [25], is the first anti-nsp10 antibody reported for use in flow cytometry and, in particular, on infected cells. Many other antibodies described here cover SARS-CoV-2 non-structural proteins that have been of great interest due to their important role in the immune response: nsp1 that functions as a virulence factor inhibiting host translation [26,27] and resulting in modulation of host immune functions [28], and nsp8 and nsp9 that interfere with IFN response [29].…”
Section: Discussionmentioning
confidence: 98%